No association between passive material property and cross-sectional area in human hamstring - Kosuke Hirata; Eri Miyamoto-Mikami; Noriko Kimura; Naokazu Miyamoto (Japanese Society of Physical Fitness and Sports Medicine, 2018)
The passive material properties of a muscle, as evaluated by shear or Young's modulus, can vary depending on the muscle cross-sectional area (CSA), since intramuscular compositions such as adipose tissue and connective tissue change with muscle hypertrophy and atrophy. However, the relationship remains unclear between the passive material properties and CSA of a muscle. Therefore, we examined whether passive muscle shear modulus is related to muscle CSA in the human hamstring. The shear modulus and anatomical CSA of the biceps femoris, semitendinosus, and semimembranosus were measured in 71 healthy young males with the hip flexed at 70° and knee fully extended. The shear modulus of each muscle was measured using ultrasound shear wave elastography. Muscle CSA was assessed using panoramic ultrasound imaging. There were individual differences in muscle shear modulus as well as muscle CSA. The coefficients of variation (CVs) of muscle shear modulus were 41.4% (range: 8.8 - 54.3 kPa), 33.0% (range: 8.4 - 57.3 kPa), and 41.1% (range: 18.2 - 107.1 kPa) for the biceps femoris, semitendinosus, and semimembranosus, respectively. There were no significant correlations between shear modulus and CSA in each or overall hamstring muscle (absolute r < 0.113). The present findings indicate that, although the passive material property of muscle is not the same among individuals, it is substantially independent of the muscle CSA, at least in the hamstring.